2016
DOI: 10.1177/0883073816664670
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Treatment of Neonatal Status Epilepticus Improves Outcome

Abstract: We aimed to decrease practice variation in treatment of neonatal status epilepticus by implementing a standardized protocol. Our primary goal was to achieve 80% adherence to the algorithm within 12 months. Secondary outcome measures included serum phenobarbital concentrations, number of patients progressing from seizures to status epilepticus, and length of hospital stay. Data collection occurred for 6 months prior and 12 months following protocol implementation. Adherence of 80% within 12 months was partially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 36 publications
0
42
0
1
Order By: Relevance
“…Additionally, there was a reduction in mean maximum serum phenobarbital concentration (41.0 vs 56.8ug/ml) as intended and a 10% reduction in seizures progressing to status epilepticus. 40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there was a reduction in mean maximum serum phenobarbital concentration (41.0 vs 56.8ug/ml) as intended and a 10% reduction in seizures progressing to status epilepticus. 40 …”
Section: Resultsmentioning
confidence: 99%
“…Observed causes of variation and delays included failure to correctly identify time of seizure onset, inconsistent physician orders, delayed decision making regarding when to administer drugs, lack of standing orders for medication as needed, varying experience of staff and personnel, knowledge gaps, inefficient communication, and issues with availability of antiepileptic medication. [38][39][40] All three studies chose to standardize treatment by creating or modifying a treatment protocol. Following employment of a linear, single-agent protocol for pediatric patients presenting with impending status epilepticus, 93% (51 of 55) of seizures were appropriately treated with first-line midazolam and 86% (6 of 7) were appropriately treated with phenytoin as second-line therapy (no comparison group available).…”
Section: Choice and Dosing Of Agentsmentioning
confidence: 99%
“…However, there is evidence that NeuroNICUs have changed practices and improved care in ways that are likely to impact neurodevelopmental outcomes and may positively impact families by reducing exposure to sedating medications and by reducing length of hospital stay. [30][31][32][33] Bashir et al describe a significant improvement in electrographic seizure detection, lower phenobarbital burden, and less anticonvulsant therapy at discharge associated with a clinical protocol in their neurocritical care program that used cEEG for 72 hours in all babies with HIE. 30 Similar findings were seen in an earlier study by Wietstock et al who reported that implementation of a neonatal neurocritical care service was associated with a reduction in cumulative phenobarbital dose, shorter duration of maintenance dosing, less medication use at discharge, and a shorter length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Haris’ group also used strategies focused on planning and educating, but did not rely as heavily on restructuring healthcare delivery at their institution. With the development of a protocol for management of neonatal status epilepticus, they were able to significantly decrease the progression of seizures from 46% to 36% of patients, serum phenobarbital concentration from 56.8 micrograms/mL to 41micrograms/mL, and length of stay by 9.7 days in survivors (23). …”
Section: Application Of Implementation Strategies In Pediatric Neurocmentioning
confidence: 99%